The synthesis and dielectric characterization of liquid crystalline hydrogen bonded complex of 3-(4-(dimethyl amino) phenyl)-1-(4-hydroxyphenyl) prop-2-en-1-one with 8-(4-cyanobiphenyl-4'-oxy) octan-1-ol - Korkmaz, Burak; Ozerol, Esma Ahlatcioglu; Gursel, Yesim; Senkal, Bahire Filiz; Okutan, Mustafa (ELSEVIER, 2018)
A new chalcone based nematic schlieren texture liquid crystalline material was prepared from 3-(4-(dimethyl amino) phenyl)-1-(4-hydroxyphenyl) prop-2-en-1-one (DMAC) and 8-(4-cyanobiphenyl-4'-oxy) octan-1-ol (LC8) by molecular self-assembly processes via hydrogen bond formation between tertiary amine group of DMAC and hydroxyl group of the LC8. Hydrogen bond formation was observed by FTIR spectroscopy. Dielectric properties of DMAC has been studied by impedance spectroscopy. The Cole-Cole analysis was used to determine the Resistance-Capacitance (RC) components equivalent circuit situation of doped LC8 on the DMAC. Dependent angular frequency variation of dielectric parameters and ac conductivity properties are non-Debye type relaxation mechanism of interfacial dopant in the liquid crystal molecular structure of the reorientation polarization effects. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Chalcone; Liquid crystal; Hydrogen bonding; Dielectric properties; DERIVATIVES; POLYMERS; SYSTEMS; DESIGN; Chemistry; Physics